2017
DOI: 10.1186/s13287-017-0531-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 primes human mesenchymal stem cells towards an anti-inflammatory and pro-trophic phenotype in vitro

Abstract: BackgroundInflammation is a key contributor to central nervous system (CNS) injury such as stroke, and is a major target for therapeutic intervention. Effective treatments for CNS injuries are limited and applicable to only a minority of patients. Stem cell-based therapies are increasingly considered for the treatment of CNS disease, because they can be used as in-situ regulators of inflammation, and improve tissue repair and recovery. One promising option is the use of bone marrow-derived mesenchymal stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 66 publications
(77 reference statements)
6
156
0
1
Order By: Relevance
“…These processes are likely to act on RNA‐dependent and RNA‐independent elements of FUS‐related pathology . Transplanted bone marrow derived stem cells were shown to secrete such anti‐inflammatory cytokines and growth factors, as IL‐10, vascular endothelial growth factor (VEGF), insulin‐like growth factor‐1 (IGF‐1), hepatocyte growth factor (HGF), brain‐derived neurotrophic factor (BDNF), neuronal growth factor (NGF), and others . This secretion was shown to be condition‐dependent, and in particular, the presence of inflammation was found to stimulate the release of the anti‐inflammatory molecules .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes are likely to act on RNA‐dependent and RNA‐independent elements of FUS‐related pathology . Transplanted bone marrow derived stem cells were shown to secrete such anti‐inflammatory cytokines and growth factors, as IL‐10, vascular endothelial growth factor (VEGF), insulin‐like growth factor‐1 (IGF‐1), hepatocyte growth factor (HGF), brain‐derived neurotrophic factor (BDNF), neuronal growth factor (NGF), and others . This secretion was shown to be condition‐dependent, and in particular, the presence of inflammation was found to stimulate the release of the anti‐inflammatory molecules .…”
Section: Discussionmentioning
confidence: 99%
“…Transplanted bone marrow derived stem cells were shown to secrete such anti‐inflammatory cytokines and growth factors, as IL‐10, vascular endothelial growth factor (VEGF), insulin‐like growth factor‐1 (IGF‐1), hepatocyte growth factor (HGF), brain‐derived neurotrophic factor (BDNF), neuronal growth factor (NGF), and others . This secretion was shown to be condition‐dependent, and in particular, the presence of inflammation was found to stimulate the release of the anti‐inflammatory molecules . Given that FUS protein is considered to be functionally related with insulin/IGF‐signaling pathway, an important element of which is BDNF, a ligand of TrkB receptor, which regulates the mechanisms of cellular stress, it can be suggested that paracrine secretion of Neuro‐Cells cytokines and growth factors may underlie the anti‐inflammatory and antidegenerative changes observed in the FUS‐tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…In one experimental setting, UCMSCs were stimulated with pro-inflammatory cytokines (hereafter referred to as 'primed') for 48 h when they reached 80% confluence. They were treated with an inflammatory cocktail containing 5 ng/mL TNF-α, 2.5n g/mL IFN-γ and 2.5 ng/mL IL-1β (Peprotech, London, UK) [11,14,15]. Figure 1 outlines the experimental plan and culture conditions of UCMSCs.…”
Section: Pro-inflammatory Priming Of Ucmscsmentioning
confidence: 99%
“…Given the varying stages of degeneration and microenvironments that exist in vivo, it will be important to tailor or design treatments for individuals. One way to achieve this could be to condition stem cells prior to implantation by acclimatizing them to patient specific in vivo microenvironmental milieu, which may include inflammatory cytokines, acidity, oxygen or nutrient deprivation . These treatments must be assessed using appropriate in vitro and ex vivo culture conditions which mimic those of the degenerate niche to assess the likely behavior and survival of transplanted cells prior to progressing to in vivo testing …”
Section: Optimizing Cell Sources and Delivery Techniquesmentioning
confidence: 99%